All You Can Eat dalam Tinjauan Maslahah al-Mursalah : Implikasi Hukum Islam terhadap Praktik Bisnis Modern - ubaidillah, ubaidillah; Nurohman, Dede; Muhtadi Anshor, Ahmad (Tasyri' : Journal of Islamic Law, 2025)
The "All You Can Eat" (AYCE) business practice has become a popular business model among the public, especially in the culinary sector. However, this phenomenon raises a number of questions related to halalness and sustainability from an Islamic legal perspective. This research aims to analyze AYCE buying and selling practices through a review Maslahah al-Mursalah (benefits that are not directly explained in the text) as an approach in Islamic law. The method used is qualitative analysis with a normative approach that examines fiqh principles and maslahah theory to assess whether AYCE practices bring benefits to individuals and society. This research found that although AYCE can provide economic benefits for entrepreneurs and satisfaction for consumers, there are potential losses in the aspects of waste (israf), nutritional imbalances, and impacts on health that must be avoided. In perspective Maslahah al-Mursalah AYCE practices can be justified if the principles of welfare and sustainability are maintained, but there needs to be strict regulation to ensure that no party is harmed and that excessive consumption can be avoided. This research concludes that the application of principles Maslahah al-Mursalah In business, AYCE can potentially provide benefits as long as it is in accordance with the values ​​of justice and balance in Islam.